Identifying the trade-offs and synergies of land use functions and their influencing factors of Lanzhou-Xining urban agglomeration in the upper reaches of Yellow River Basin, China - Jun Ren; Rongrong Ma; Yuhan Huang; Quanxi Wang; Jing Guo; Chengying Li; Wei Zhou (Ecological Indicators, 2024)
Identifying the interactions of land use functions (LUFs) is of great significance for alleviating the contradiction between human and land, and promoting sustainable use of land resources. However, few studies concerned the interactions of LUFs in urban agglomerations of ecologically fragile areas in China at a fine scale. In this study, we constructed a quantitative and visualized evaluation system of LUFs that conforms to three primary functions, ten sub-functions, and nineteen indicators of Lanzhou-Xining urban agglomeration (LXUA) in the upper reaches of the Yellow River basin based on the production-living- ecological functions. Then, the comprehensive evaluation method, hot spot analysis, and geographic weighted regression (GWR) model were used to identify the interactions among LUFs and influencing factors of LXUA from 2000 to 2020 at the county and grid scales. The results show that the LXUA is dominated by ecological function (EF), and EF and living function (LF) showing a “U” shaped change feature, while production function (PF) show an inverted “U” shaped change feature. Meanwhile, the cold spots and hot spots of PF and EF present the spatial characteristic of “overall dispersion and local aggregation”, while the LF has no cold spots, and the hot spots present the spatial characteristic of “point-axis”. Moreover, the PF and LF are in a synergistic relationship at two scales, with complementarity in space, while the EF and PF and the PF and LF are both in a trade-offs relationship, with overlap in space. Finally, socioeconomic development factors have remarkable impact on LUFs at the county scale, while LUFs at the grid scale is the comprehensive result of natural conditions, socioeconomic factors, accessibility and political factors. The results can provide references for the LXUA to differentiated design the land use policy, and provide empirical case for other ecologically fragile areas to alleviate the trade-offs of LUFs.